2014
DOI: 10.1128/jvi.03022-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Form of Rotavirus NSP2 and Phosphorylation-Dependent NSP2-NSP5 Interactions Are Associated with Viroplasm Assembly

Abstract: Rotavirus (RV) replication occurs in cytoplasmic inclusions called viroplasms whose formation requires the interactions of RV proteins NSP2 and NSP5; however, the specific role(s) of NSP2 in viroplasm assembly remains largely unknown. To study viroplasm formation in the context of infection, we characterized two new monoclonal antibodies (MAbs) specific for NSP2. These MAbs show high-affinity binding to NSP2 and differentially recognize distinct pools of NSP2 in RV-infected cells; a previously unrecognized cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 49 publications
(66 reference statements)
7
98
0
3
Order By: Relevance
“…IF images were acquired using a Nikon A1-R confocal laser scanning microscope as previously described (Criglar et al, 2014). The images for the biopsy sections along with their corresponding controls were captured using identical parameters to allow comparison between the antibodies and the pre-immune sera.…”
Section: Haematoxylin and Eosin And Immunofluorescence Staining Of Inmentioning
confidence: 99%
“…IF images were acquired using a Nikon A1-R confocal laser scanning microscope as previously described (Criglar et al, 2014). The images for the biopsy sections along with their corresponding controls were captured using identical parameters to allow comparison between the antibodies and the pre-immune sera.…”
Section: Haematoxylin and Eosin And Immunofluorescence Staining Of Inmentioning
confidence: 99%
“…Its main function is to participate in the formation of viroplasms, which are cytoplasmic structures where genome replication and morphogenesis of new particles occurs (Criglar et al 2014). Among porcine strains, previous data showed low rates of genetic variability NSP5/6, because their structural and functional constraints and lower exposure to immune selection (Barbosa et al 2013), which is a desirable property when selecting targets for nucleic acid detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of NSP2 to these sites could interfere with the assembly of VP2 into core structures. Recently, a new cytoplasmic form of NSP2 has been characterized that interacts with cellular and viral proteins, including VP2 (60). Based on our results and the previous observations, which showed that purified NSP2 impedes viral replication in vitro by interfering with the role of VP2 in forming the minus-strand initiation complex (63), a reasonable hypothesis is that NSP2-VP2 interactions, among other functions, play a role in preventing the premature assembly of VP2 cores in the cytoplasm, prior to VP2 being shuttled into the viroplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Direct interaction of NSP2 and VP2, although suspected, has not been demonstrated previously. Previous studies showing that high levels of NSP2 are associated with RIs recovered from infected cells that specifically contained VP2 (21) and more recent studies showing that VP2 is pulled down by NSP2 from the lysates of rotavirus-infected cells strongly suggest a possible interaction between the two proteins (60). We hypothesized that in addition to VP1, NSP2 directly binds VP2, possibly coordinating the VP2- The peptide sequences corresponding to the spots denoted 1 to 18 in panel B that showed intensities higher than the 60% cutoff.…”
Section: Interaction Of Nsp2 With Vp1mentioning
confidence: 99%